Strategi Pengelolaan Inventory Pada Proses Penerimaan, Penyimpanan, Dan Pengeluaran Barang Umum Di Pt. Semen Padang - Shinta Adellia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inventory management is a crucial aspect in supporting the smooth operation of a company, particularly in the cement industry, which has a complex material flow. This study aims to analyze inventory management strategies in the process of receiving, storing, and issuing general goods at PT Semen Padang. The research methods used include field studies, interviews, and descriptive analysis of existing inventory management procedures. The results show that the implementation of an integrated recording system, efficient warehouse layout, and stock control using the First In First Out (FIFO) and Reorder Point methods can minimize the risk of excess or shortage of inventory. In addition, regular monitoring and consistent implementation of standard operating procedures (SOPs) increase the effectiveness of the process of receiving, storing, and issuing goods. The conclusion of this study is that an appropriate inventory management strategy can improve internal supply chain efficiency, reduce storage costs, and ensure the availability of goods to support the continuity of PT Semen Padang's production.